Development of the Landscape Elements in the Asia Afrika Historic Corridor in Bandung City - Izzati, Husna; Galupamudia, Nutrian (Universitas Syiah Kuala, 2024)
Asia Afrika Road in Bandung is a historically significant area known for its colonial architecture, serving as a key destination for historical tourism area. The road and its surrounding area are a single interconnected space that forms the image of this area. Landscape processing in the Asia Afrika Corridor by combining its constituent elements is essential to create this image. Then, how is the composition, and what are the elements of the landscape that influence the Asia Afrika Corridor? This study uses a qualitative approach to the case study type, emphasizing the exploratory method. Archival documentation studies support the emphasis on analyzing primary data to produce a mapping in periodization. The research applies urban landscape and corridor theory, dividing the corridor into three segments and identifying five main elements that shape its landscape over time. Findings reveal that while the road network maintains a consistent form, the characteristics of building facades, pedestrian pathways, street furniture, and green spaces vary across the segments. Overall, the development of all the existing elements cannot be separated from the historical journey of the Asia Afrika Corridor.